Protein requirements and soybean meal products replacement for feed development of hybrid grouper, (Epinephelus fuscoguttatus X Epinephelus lanceolatus) - Norfazreena Mohd Faudzi (2019)
Hybrid grouper (Epinephelus fuscoguttatus ¥ x E lanceo!atus o) is one of the most popular aquaculture fish among grouper production. In order to develop a feed for hybrid grouper, three feeding experiments were conducted. Experiment 1 was conducted to determine the optimum protein and protein-sparing effect by dietary lipid in the feed for the hybrid grouper. The hybrid grouper juveniles (body weight, BW 6.6±0. lg) were fed with 12 experimental feed containing different levels of protein (45, SO and 55%) and lipid (8, 12, 16 and 20%) for 12 weeks. Experiment 2 was conducted to investigate the optimum level of soy protein concentrate (SPC) in replacement of fish meal (FM) for hybrid grouper. Six isoproteic (50% crude protein, CP) and isolipidic (12% crude lipid, CL) feed formulated to replace 20%, 30%, 40%, 50% and 60% of FM protein with SPC and a control feed without SPC were fed to triplicate groups of fish with initial BW 6.1±0.7g for 6 weeks. Experiment 3 was conducted to evaluate the supplementation of phytase in SPC and defatted soybean meal (DSM) based feed for hybrid grouper. Isoproteic (50% CP) and isolipidic (12% CL) feed were formulated with 30% of SPC or DSM protein at five levels of phytase supplementation 0, 1000, 2000, 3000 and 4000 FTU/kg and feed with 100% of FM protein served as control feed. The feeds were fed to fish with initial BW 6.2±0.0g and 5.8±0. lg for 12 weeks. All of the fish were fed with experimental feed until apparent satiation level two times daily and growth was monitored at two weeks interval. At the end of all the experiments, final BW and number of fish were recorded and some fish (n=6) from each treatment were sacrificed for body indices and biochemical analysis. Apparent digestibility coefficient (ADC) for all the trials was conducted at the end of the feeding trial. The fish intestine was sampled in Experiment 3 for histological observation. The growth of hybrid grouper in Experiment 1 showed an increasing trend when dietary protein and lipid levels increased from 45% to 55% and 8% to 16%, respectively. However, growth of fish fed with 20% of lipid was lower than those fed with 16% of lipid regardless of protein levels. Protein-sparing effect can be observed when dietary lipid increased from 8 to 16% in feed for hybrid grouper. No significant effect of increasing dietary protein and lipid levels was observed on the ADC of protein and lipid. Regression analysis on NPU showed that 50% dietary protein in combination of 16.5% dietary lipid is recommended for the hybrid grouper. Experiment 2 demonstrated that FM was able to be replaced partially up to 50% with SPC protein without significantly affected the growth performance. However, increasing the SPC level from 30% to 60% led to higher FCR and lower PER and NPU value compared to SPC0 and SPC20. In addition, the ADCs of protein and lipid decreased when the inclusion level of SPC increased from 0% to 60%. Regression analysis on specific growth rate suggested that highest growth of hybrid grouper was demonstrated at 21.4% replacement of SPC. In the Experiment 3, the growth of fish fed with SPC and DSM based feed with or without phytase was higher than fish fed control feed. The survival and intestine condition were not affected by the SPC and DSM feed. However, fish fed DSM based feed showed significantly higher feed intake, and lower NPU and ADC protein compared to control feed. The study indicates that hybrid grouper can utilize 30% of SPC and DSM protein replacement without phytase supplementation. Overall, the present study contributes to the current understanding on protein and sparing effect by dietary lipid and the use of soybean meal products in developing feed for hybrid grouper.